3(-2m+5)=-4m+9-m

Simple and best practice solution for 3(-2m+5)=-4m+9-m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2m+5)=-4m+9-m equation:


Simplifying
3(-2m + 5) = -4m + 9 + -1m

Reorder the terms:
3(5 + -2m) = -4m + 9 + -1m
(5 * 3 + -2m * 3) = -4m + 9 + -1m
(15 + -6m) = -4m + 9 + -1m

Reorder the terms:
15 + -6m = 9 + -4m + -1m

Combine like terms: -4m + -1m = -5m
15 + -6m = 9 + -5m

Solving
15 + -6m = 9 + -5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5m' to each side of the equation.
15 + -6m + 5m = 9 + -5m + 5m

Combine like terms: -6m + 5m = -1m
15 + -1m = 9 + -5m + 5m

Combine like terms: -5m + 5m = 0
15 + -1m = 9 + 0
15 + -1m = 9

Add '-15' to each side of the equation.
15 + -15 + -1m = 9 + -15

Combine like terms: 15 + -15 = 0
0 + -1m = 9 + -15
-1m = 9 + -15

Combine like terms: 9 + -15 = -6
-1m = -6

Divide each side by '-1'.
m = 6

Simplifying
m = 6

See similar equations:

| 10+0.07(15x)+9=15x | | 3x+8(2x-6)=2+12x | | 10x^2+1000=0 | | 3y-4=4 | | (22x)(x)+8x+840=0 | | 11(7)-3=7(7)+25 | | 4x^2-5=43 | | 0.4x-1.2=0.15+1.8 | | 16+8m-4+2m=22 | | 10x+1000=0 | | 12x+60-28=9-12x | | 3x+8(2+6)=2+12x | | -6x+(-30)=24 | | 3y-0=4 | | 4x+20=7x-40 | | 10+4*a=3a | | -x-4+2x=2x+5-2x | | 16=x(2) | | 7+2(4x+2)+2x=20 | | 22x+8x+840=0 | | 1.1x+2.6=0.6x+1.25 | | 16=xsquared | | 4x+20=5x-40 | | 2n^2+2n-180= | | 3x^3+20x^2-59x+36=0 | | 28-x^2+3x=0 | | -x^2+4=2x | | n^2+2n-180=0 | | .05b=2b | | 2(-4)+y=4 | | 3(3-2)+8*2=27-4*2 | | -16x^2+32x+20=0 |

Equations solver categories